PPS / LCP composition and preparation method thereof

By adopting PPS/LCP composition and combining functionalized multi-wall carbon nanotubes and alkaline copper phosphate and other materials, the problems of high dielectric constant, limited color and heavy metal pollution in the prior art are solved, and high performance, low dielectric and environmentally friendly PPS/LCP compositions are achieved.

CN119859405AActive Publication Date: 2025-04-22GUANGDONG ALDEX NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411952401.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-22
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The PPS compositions used for direct laser molding in the prior art have problems such as high dielectric constant, limited color and heavy metal pollution, which are difficult to meet the needs of some color and environmentally friendly high-performance materials.

Method used

By combining the PPS/LCP composition, the dielectric constant is reduced and the mechanical properties and laser direct moldability of the material are improved by combining the functionalized multi-wall carbon nanotubes and alkaline copper phosphate.

Benefits of technology

It realizes PPS/LCP compositions with excellent mechanical properties, flame retardant properties, laser direct moldability and low dielectric properties, suitable for 5G devices and other electronic and electrical components, and is environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215157230000021
    Figure BDA0005215157230000021
  • Figure BDA0005215157230000121
    Figure BDA0005215157230000121
  • Figure FDA0005215157220000011
    Figure FDA0005215157220000011
Patent Text Reader

Abstract

The invention discloses a PPS / LCP (polyphenylene sulfide / liquid crystal polymer) composition and a preparation method thereof. The PPS / LCP composition is prepared from the following components in parts by weight: 43-64 parts of PPS resin, 5-15 parts of LCP resin, 15-25 parts of special glass fibers, 5-10 parts of a laser sensitizer A, 1-5 parts of a laser sensitizer B, 2-5 parts of a compatilizer, 1-3 parts of a coupling agent and 0.2-0.6 part of an antioxidant. Wherein the laser sensitizer A is a functionalized multi-walled carbon nanotube, and the laser sensitizer B is any one of basic copper phosphate, copper chromite black, zinc hydroxystannate and tin oxide. The invention provides the low-dielectric PPS / LCP composition which has excellent mechanical property and flame retardant property and can be directly formed by laser, the PPS is compounded with the LCP to reduce the dielectric constant of the composition, and the polyphenylene sulfide and the liquid crystal polymer mutually complement each other, so that the toughness and crystallization rate of the PPS are improved, and the strength and rigidity of the LCP are improved, and therefore, the composition has excellent comprehensive performance. Basic copper phosphate and functionalized multi-walled carbon nanotubes are compounded to improve the laser direct formability of the PPS / LCP composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, in particular to a PPS / LCP composition and a preparation method thereof. Background Art

[0002] The LDS (laser direct structuring) process is a professional 3D-MID (Three-dimensional Moulded Interconnect Device) production technology that combines laser processing, injection and electroplating processes. It mainly uses CNC lasers to directly transfer circuit patterns to the surface of molded plastic components, and uses the three-dimensional surface of the three-dimensional workpiece to form a circuit interconnect structure. This process usually includes steps such as injection molding, laser activation, electroplating, spraying / assembly and RF testing. It has been widely used in the fields of mobile phone antennas, three-dimensional circuits, smart sensors, such as wearable devices, smart medical devices, driverless cars, smart homes, drones, etc., and is one of the key technologies to achieve light, thin and miniaturized smart terminals.

[0003] Polyphenylene sulfide (PPS) has the advantages of high temperature resistance, corrosion resistance, radiation resistance, non-staining, non-toxicity, excellent mechanical and electrical properties, and good product dimensional stability. The linear rigid structure formed by the direct connection of the benzene ring with the sulfur atom in the para position of the PPS molecular chain has a high degree of crystallinity and excellent dimensional stability and rigidity. It is known as the sixth general engineering plastic after the five major general engineering plastics. However, the structure of polyphenylene sulfide determines its disadvantages of being hard and brittle. Liquid crystal polymer (LCP) is a crystalline material in the molten state with very good fluidity, chemical stability, mechanical strength, electrical insulation properties and thermal stability, but LCP has the disadvantages of poor strength, rigidity and heat resistance when used alone.

[0004] At present, some research has been done on laser forming PPS compositions in the prior art. For example, Chinese patent CN109852051A discloses a nylon / polyphenylene sulfide alloy material and its preparation method, which comprises components: 35-80 parts of nylon, 1-10 parts of polyphenylene sulfide, and 20-50 parts of glass fiber. It can be seen that the prior art mainly involves ordinary glass fiber reinforced PPS-based LDS materials, and the LDS additive used is a spinel structure oxide containing copper and chromium. The oxide contains heavy metal chromium, which will cause environmental pollution. In addition, copper chromium oxide can only provide black color, which limits the application of LDS technology in many fields, especially in some fields with high color requirements. Summary of the invention

[0005] In view of this, the present invention provides a PPS / LCP composition and a preparation method thereof. The composition has excellent mechanical properties, flame retardant properties, laser direct formability and low dielectric properties, and can be widely used in 5G devices, electronic and electrical components, etc.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] In a first aspect, the present invention discloses a PPS / LCP composition, which is prepared from the following components in parts by weight:

[0008]

[0009] The laser sensitizer A is a functionalized multi-walled carbon nanotube, and the laser sensitizer B is any one of basic copper phosphate, copper chromium black, zinc hydroxystannate, and tin oxide.

[0010] As a further solution of the present invention: the number average relative molecular mass of the PPS resin is 15000-25000.

[0011] As a further solution of the present invention: the LCP resin is a thermotropic liquid crystal polymer.

[0012] As a further solution of the present invention: the dielectric constant of the special glass fiber is 3.5-4.0, the cross-section length is 26-30 μm, the width is 6.5-7.5 μm, and the flatness ratio is 4:1.

[0013] As a further solution of the present invention: the compatibilizer is double-grafted SEBS; the double-grafted SEBS is hydrogenated styrene-butadiene-styrene copolymer double-grafted with glycidyl methacrylate and maleic anhydride.

[0014] As a further solution of the present invention: the coupling agent is γ-aminopropyltriethoxysilane; the antioxidant is bis(2,4-dicumylphenyl)pentaerythritol diphosphite.

[0015] As a further solution of the present invention: the preparation method of the functionalized multi-walled carbon nanotubes is as follows:

[0016] (1) evenly dispersing multi-walled carbon nanotubes and nano zinc oxide in anhydrous ethanol at a mass ratio of 100:10-20, and filtering to obtain an intermediate product;

[0017] (2) The intermediate product is mixed with an acrylic acid solution, butyl titanate, and an aqueous ammonium persulfate solution, and the mixture is vacuumed and reacted at 90-100° C. in a nitrogen atmosphere for 2-4 hours. After cooling to room temperature, the reaction product is washed, filtered, and dried to obtain functionalized multi-walled carbon nanotubes.

[0018] As a further solution of the present invention: in the acrylic acid solution, the volume ratio of acrylic acid, deionized water and anhydrous ethanol is 1:(0.3-0.5):(0.2-0.4); the mass concentration of the ammonium persulfate aqueous solution is 4-6wt%.

[0019] As a further solution of the present invention: in step (2), the mass ratio of the intermediate product, acrylic acid solution, butyl titanate, and ammonium persulfate aqueous solution is 100:(450-500):(1-3):(2-5).

[0020] On the other hand, the present invention discloses a method for preparing the above-mentioned PPS / LCP composition, comprising the following steps:

[0021] (1) PPS resin, LCP resin, double-grafted SEBS and bis(2,4-dicumylphenyl)pentaerythritol diphosphite are uniformly mixed to obtain a first mixed material;

[0022] (2) mixing the functionalized multi-walled carbon nanotubes, basic copper phosphate, and γ-aminopropyltriethoxysilane to obtain a second mixture;

[0023] (3) adding the first mixed material into the main feed port of a parallel twin-screw extruder, adding the second mixed material into the side of the extruder, and adding special glass fiber into the other side, performing melt extrusion, and granulation to obtain a PPS / LCP composition;

[0024] Among them: the temperature of zone 1 is 300-310°C, the temperature of zone 2 is 300-310°C, the temperature of zone 3 is 305-315°C, the temperature of zone 4 is 305-315°C, the temperature of zone 5 is 310-320°C, the temperature of zone 6 is 310-320°C, the temperature of zone 7 is 315-325°C, the temperature of zone 8 is 315-325°C, the temperature of die head is 310-320°C, and the screw speed is 400-600rpm.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The present invention provides a low dielectric PPS / LCP composition with excellent mechanical properties, flame retardant properties, and laser direct forming. It innovatively proposes to use PPS to compound LCP to reduce the dielectric constant of the composition, and polyphenylene sulfide and liquid crystal polymer complement each other, which not only improves the toughness and crystallization rate of PPS, but also improves the strength and rigidity of LCP, thus having excellent comprehensive performance. Basic copper phosphate and functionalized multi-walled carbon nanotubes are compounded to improve the laser direct forming of the PPS / LCP composition.

[0027] 2. The present invention creatively proposes a preparation process for multi-walled carbon nanotubes modified by the surface of nano zinc oxide, which not only improves the compatibility of multi-walled carbon nanotubes in the resin matrix, but also significantly improves the laser direct forming property of the PPS / LCP composition by adding it into the PPS / LCP resin matrix.

[0028] 3. Synergistic effect of laser sensitizer A and laser sensitizer B. The present invention utilizes the Cu / Zn / Sn formed after the laser sensitizer B is excited, which has good absorption performance for lasers of different wavelengths, and is conducive to LDS forming. After compounding with functionalized multi-walled carbon nanotubes, on the one hand, the Zn formed by laser irradiation on the surface of the functionalized multi-walled carbon nanotubes also has good absorption performance for lasers. In addition, the multi-walled carbon nanotubes themselves have a certain conductivity, which can promote the formation of a conductive network and further promote the formation of a conductive pattern, so that the composite material has a better laser forming function. DETAILED DESCRIPTION

[0029] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0031] The specific information of the raw materials used in the following examples and comparative examples is as follows:

[0032] Polyphenylene sulfide resin, number average relative molecular mass of 20,000, carboxyl terminated, purchased from Zhejiang Xinhecheng Special Materials Co., Ltd.;

[0033] Special glass fiber with a dielectric constant of 3.8 (1 GHz), a cross-section length of 28 μm, a width of 7 μm, and an aspect ratio of 4:1, was purchased from Chongqing International Composite Materials Co., Ltd.;

[0034] Ordinary reinforced glass fiber, dielectric constant 7.0 (1GHz), fiber diameter 14μm, purchased from Chongqing International Composite Materials Co., Ltd.;

[0035] Double-grafted SEBS, with a grafting rate of 1.2 wt % of glycidyl methacrylate and 1.2 wt % of maleic anhydride, was purchased from Shenyang Ketong Plastic Co., Ltd.;

[0036] Basic copper phosphate, particle size 0.2 μm, purchased from Merck Chemical Technology (Shanghai) Co., Ltd.;

[0037] Copper chrome black, Black 28, was purchased from Hubei Jincheng New Materials Co., Ltd.;

[0038] Zinc hydroxystannate was purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0039] Tin oxide, particle size 50 nm, purchased from Nanjing Kelinston Chemical Technology Co., Ltd.;

[0040] γ-Aminopropyltriethoxysilane was purchased from Nanjing Nengde New Materials Technology Co., Ltd.;

[0041] Multi-walled carbon nanotubes were purchased from LG, South Korea;

[0042] Butyl titanate was purchased from Shandong Hui'an Chemical Co., Ltd.

[0043] Ammonium persulfate, purchased from Jinan 168 Chemical Co., Ltd.;

[0044] Bis(2,4-dicumylphenyl)pentaerythritol diphosphite was purchased from Hubei Zhonglong Kangsheng Fine Chemical Co., Ltd.

[0045] All materials are commercially available conventional products.

[0046] It is to be understood that the above raw materials and reagents are only examples of some specific embodiments of the present invention, so that the technical solution of the present invention is clearer, and it does not mean that the present invention can only use the above reagents, and the specific scope in the claims shall prevail. In addition, the "parts" described in the examples and comparative examples, unless otherwise specified, refer to parts by weight.

[0047] Any range described in the present invention includes the end value and any numerical value between the end values ​​and any sub-range formed by the end value or any numerical value between the end values.

[0048] In the examples and comparative examples, the preparation method of the functionalized carbon nanotubes used is as follows:

[0049] (1) adding 100 g of multi-walled carbon nanotubes and 15 g of nano zinc oxide into a flask, adding them into anhydrous ethanol for ultrasonic dispersion for 1 to 3 hours, and filtering to obtain a mixture;

[0050] (2) Add 500 ml of an aqueous solution of acrylic acid into a reactor, wherein the volume ratio of acrylic acid: deionized water: anhydrous ethanol is 1:0.4:0.3; then add 100 g of the mixture of step (1), 2 g of butyl titanate, and 3 ml of a 5 wt % aqueous solution of ammonium persulfate, evacuate and pass nitrogen, and control the system pressure in the reactor to be 0.3 MPa;

[0051] (3) The reaction kettle was stirred and heated to 95° C. for 3 h, and then cooled to room temperature and washed, filtered, and dried to obtain nano-oxide surface-modified multi-walled carbon nanotubes.

[0052] Example 1

[0053] The following components were weighed and set aside: 54 parts of PPS resin, 10 parts of LCP resin, 20 parts of special glass fiber, 3 parts of double-grafted SEBS, 3 parts of functionalized multi-walled carbon nanotubes, 8 parts of basic copper phosphate, 2 parts of γ-aminopropyltriethoxysilane, and 0.6 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite;

[0054] PPS resin, LCP resin, double-grafted SEBS and bis(2,4-dicumylphenyl)pentaerythritol diphosphite are added into a mixer and mixed to obtain a first mixture;

[0055] Adding functionalized multi-walled carbon nanotubes, basic copper phosphate, and γ-aminopropyltriethoxysilane into another mixer and mixing them evenly to obtain a second mixture;

[0056] The first mixed material is added into the main feeding port of the parallel twin-screw extruder through a feeder, and the second mixed material is added into the side of the extruder, and the special glass fiber is added into the other side for melt extrusion and granulation to obtain the PPS / LCP composition.

[0057] The process parameters of the parallel twin-screw extruder are: the temperature of zone 1 is 305℃, the temperature of zone 2 is 305℃, the temperature of zone 3 is 310℃, the temperature of zone 4 is 310℃, the temperature of zone 5 is 315℃, the temperature of zone 6 is 315℃, the temperature of zone 7 is 320℃, the temperature of zone 8 is 320℃, the die head temperature is 315℃, and the screw speed is 500rpm.

[0058] Example 2

[0059] The following components were weighed and set aside: 43 parts of PPS resin, 15 parts of LCP resin, 25 parts of special glass fiber, 5 parts of double-grafted SEBS, 5 parts of functionalized multi-walled carbon nanotubes, 5 parts of copper chrome black, 2 parts of γ-aminopropyltriethoxysilane, and 0.2 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite;

[0060] PPS resin, LCP resin, double-grafted SEBS and bis(2,4-dicumylphenyl)pentaerythritol diphosphite are added into a mixer and mixed evenly to obtain a first mixture;

[0061] Adding functionalized multi-walled carbon nanotubes, basic copper phosphate, and γ-aminopropyltriethoxysilane into another mixer and mixing them evenly to obtain a second mixture;

[0062] The first mixed material is added into the main feed port of the parallel twin-screw extruder, and the second mixed material is added into the side of the extruder, and the special glass fiber is added into the other side for melt extrusion and granulation to obtain the PPS / LCP composition.

[0063] Parallel twin-screw extruder process parameters: zone 1 temperature is 310℃, zone 2 temperature is 310℃, zone 3 temperature is 315℃, zone 4 temperature is 315℃, zone 5 temperature is 320℃, zone 6 temperature is 320℃, zone 7 temperature is 325℃, zone 8 temperature is 325℃, die head temperature is 320℃, screw speed is 500rpm.

[0064] Example 3

[0065] The following components were weighed and set aside: 64 parts of PPS resin, 5 parts of LCP resin, 15 parts of special glass fiber, 2 parts of double-grafted SEBS, 1 part of functionalized multi-walled carbon nanotubes, 10 parts of zinc hydroxystannate, 3 parts of γ-aminopropyltriethoxysilane, and 0.3 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite;

[0066] PPS resin, LCP resin, double-grafted SEBS and bis(2,4-dicumylphenyl)pentaerythritol diphosphite are added into a mixer and mixed evenly to obtain a first mixture;

[0067] Adding functionalized multi-walled carbon nanotubes, basic copper phosphate, and γ-aminopropyltriethoxysilane into another mixer and mixing them evenly to obtain a second mixture;

[0068] The first mixed material is added into the main feed port of the parallel twin-screw extruder, and the second mixed material is added into the side of the extruder, and the special glass fiber is added into the other side for melt extrusion and granulation to obtain the PPS / LCP composition.

[0069] The process parameters of the parallel twin-screw extruder are: the temperature of zone 1 is 295℃, the temperature of zone 2 is 295℃, the temperature of zone 3 is 300℃, the temperature of zone 4 is 300℃, the temperature of zone 5 is 310℃, the temperature of zone 6 is 310℃, the temperature of zone 7 is 320℃, the temperature of zone 8 is 320℃, the die head temperature is 320℃, and the screw speed is 400rpm.

[0070] Example 4

[0071] The following components were weighed and set aside: 59 parts of PPS resin, 10 parts of LCP resin, 20 parts of special glass fiber, 2 parts of double-grafted SEBS, 2 parts of functionalized multi-walled carbon nanotubes, 6 parts of tin oxide, 1 part of γ-aminopropyltriethoxysilane, and 0.3 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite;

[0072] PPS resin, LCP resin, double-grafted SEBS and bis(2,4-dicumylphenyl)pentaerythritol diphosphite are added into a mixer and mixed evenly to obtain a first mixture;

[0073] Adding functionalized multi-walled carbon nanotubes, basic copper phosphate, and γ-aminopropyltriethoxysilane into another mixer and mixing them evenly to obtain a second mixture;

[0074] The first mixed material is added into the main feed port of the parallel twin-screw extruder, and the second mixed material is added into the side of the extruder, and the special glass fiber is added into the other side for melt extrusion and granulation to obtain the PPS / LCP composition.

[0075] Parallel twin-screw extruder process parameters: zone 1 temperature is 300℃, zone 2 temperature is 300℃, zone 3 temperature is 305℃, zone 4 temperature is 305℃, zone 5 temperature is 310℃, zone 6 temperature is 310℃, zone 7 temperature is 320℃, zone 8 temperature is 320℃, die head temperature is 320℃, screw speed is 600rpm.

[0076] Example 5

[0077] The following components were weighed and set aside: 50 parts of PPS resin, 15 parts of LCP resin, 20 parts of special glass fiber, 4 parts of double-grafted SEBS, 2 parts of functionalized multi-walled carbon nanotubes, 7 parts of basic copper phosphate, 2 parts of γ-aminopropyltriethoxysilane, and 0.3 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite;

[0078] PPS resin, LCP resin, double-grafted SEBS and bis(2,4-dicumylphenyl)pentaerythritol diphosphite are added into a mixer and mixed evenly to obtain a first mixture;

[0079] Adding functionalized multi-walled carbon nanotubes, basic copper phosphate, and γ-aminopropyltriethoxysilane into another mixer and mixing them evenly to obtain a second mixture;

[0080] The first mixed material is added into the main feed port of the parallel twin-screw extruder, and the second mixed material is added into the side of the extruder, and the special glass fiber is added into the other side for melt extrusion and granulation to obtain the PPS / LCP composition.

[0081] The process parameters of the parallel twin-screw extruder include: zone 1 temperature is 300°C, zone 2 temperature is 300°C, zone 3 temperature is 305°C, zone 4 temperature is 305°C, zone 5 temperature is 310°C, zone 6 temperature is 310°C, zone 7 temperature is 320°C, zone 8 temperature is 320°C, die head temperature is 320°C, and screw speed is 600rpm.

[0082] Comparative Example 1

[0083] The following components were weighed and set aside: 54 parts of PPS resin, 10 parts of LCP resin, 20 parts of ordinary reinforced glass fiber, 3 parts of double-grafted SEBS, 3 parts of functionalized multi-walled carbon nanotubes, 8 parts of basic copper phosphate, 2 parts of γ-aminopropyltriethoxysilane, and 0.6 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite;

[0084] PPS resin, LCP resin, double-grafted SEBS and bis(2,4-dicumylphenyl)pentaerythritol diphosphite are added into a mixer and mixed evenly to obtain a first mixture;

[0085] Adding functionalized multi-walled carbon nanotubes, basic copper phosphate, and γ-aminopropyltriethoxysilane into another mixer and mixing them evenly to obtain a second mixture;

[0086] The first mixed material is added into the main feed port of the parallel twin-screw extruder, and the second mixed material is added into the side of the extruder, and ordinary glass fiber is added into the other side for melt extrusion and granulation to obtain the PPS / LCP composition.

[0087] Parallel twin-screw extruder process parameters: zone 1 temperature is 305℃, zone 2 temperature is 305℃, zone 3 temperature is 310℃, zone 4 temperature is 310℃, zone 5 temperature is 315℃, zone 6 temperature is 315℃, zone 7 temperature is 320℃, zone 8 temperature is 320℃, die head temperature is 315℃, screw speed is 500rpm.

[0088] Comparative Example 2

[0089] The following components were weighed and set aside: 64 parts of PPS resin, 20 parts of special glass fiber, 3 parts of double-grafted SEBS, 3 parts of functionalized multi-walled carbon nanotubes, 8 parts of basic copper phosphate, 2 parts of γ-aminopropyltriethoxysilane, and 0.6 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite;

[0090] PPS resin, di-grafted SEBS and bis(2,4-dicumylphenyl)pentaerythritol diphosphite are added into a mixer and mixed evenly to obtain a first mixture;

[0091] Adding functionalized multi-walled carbon nanotubes, basic copper phosphate, and γ-aminopropyltriethoxysilane into another mixer and mixing them evenly to obtain a second mixture;

[0092] The first mixed material is added into the main feed port of the parallel twin-screw extruder, and the second mixed material is added into the side of the extruder, and the special glass fiber is added into the other side for melt extrusion and granulation to obtain the PPS / LCP composition.

[0093] The process parameters of the parallel twin-screw extruder include: zone 1 temperature is 305°C, zone 2 temperature is 305°C, zone 3 temperature is 310°C, zone 4 temperature is 310°C, zone 5 temperature is 315°C, zone 6 temperature is 315°C, zone 7 temperature is 320°C, zone 8 temperature is 320°C, die head temperature is 315°C, and screw speed is 500rpm.

[0094] Comparative Example 3

[0095] The following components were weighed and set aside: 54 parts of PPS resin, 10 parts of LCP resin, 20 parts of special glass fiber, 3 parts of functionalized multi-walled carbon nanotubes, 8 parts of basic copper phosphate, 2 parts of γ-aminopropyltriethoxysilane, and 0.6 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite;

[0096] PPS resin, LCP resin and bis(2,4-dicumylphenyl)pentaerythritol diphosphite are added into a mixer and mixed evenly to obtain a first mixed material;

[0097] Add functionalized multi-walled carbon nanotubes, basic copper phosphate, and γ-aminopropyltriethoxysilane into another mixer and mix them evenly to obtain a second mixture;

[0098] The first mixed material is added into the main feeding port of the parallel twin-screw extruder through a feeder, and the second mixed material is added into the side of the extruder, and the special glass fiber is added into the other side for melt extrusion and granulation to obtain the PPS / LCP composition.

[0099] Parallel twin-screw extruder process parameters: zone 1 temperature is 305℃, zone 2 temperature is 305℃, zone 3 temperature is 310℃, zone 4 temperature is 310℃, zone 5 temperature is 315℃, zone 6 temperature is 315℃, zone 7 temperature is 320℃, zone 8 temperature is 320℃, die head temperature is 315℃, screw speed is 500rpm.

[0100] Comparative Example 4

[0101] The following components were weighed and set aside: 54 parts of PPS resin, 10 parts of LCP resin, 20 parts of special glass fiber, 3 parts of double-grafted SEBS, 3 parts of multi-walled carbon nanotubes, 8 parts of basic copper phosphate, 2 parts of γ-aminopropyltriethoxysilane, and 0.6 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite;

[0102] PPS resin, LCP resin, double-grafted SEBS and bis(2,4-dicumylphenyl)pentaerythritol diphosphite are added into a mixer and mixed evenly to obtain a first mixture;

[0103] Add multi-walled carbon nanotubes, basic copper phosphate, and γ-aminopropyltriethoxysilane into another mixer and mix them evenly to obtain a second mixture;

[0104] The first mixed material is added into the main feeding port of the parallel twin-screw extruder through a feeder, and the second mixed material is added into the side of the extruder, and the special glass fiber is added into the other side for melt extrusion and granulation to obtain the PPS / LCP composition.

[0105] Parallel twin-screw extruder process parameters: zone 1 temperature is 305℃, zone 2 temperature is 305℃, zone 3 temperature is 310℃, zone 4 temperature is 310℃, zone 5 temperature is 315℃, zone 6 temperature is 315℃, zone 7 temperature is 320℃, zone 8 temperature is 320℃, die head temperature is 315℃, screw speed is 500rpm.

[0106] Comparative Example 5

[0107] The following components were weighed and set aside: 54 parts of PPS resin, 10 parts of LCP resin, 20 parts of special glass fiber, 3 parts of double-grafted SEBS, 11 parts of functionalized multi-walled carbon nanotubes, 2 parts of γ-aminopropyltriethoxysilane, and 0.6 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite;

[0108] PPS resin, LCP resin, double-grafted SEBS and bis(2,4-dicumylphenyl)pentaerythritol diphosphite are added into a mixer and mixed to obtain a first mixture;

[0109] Adding functionalized multi-walled carbon nanotubes and γ-aminopropyltriethoxysilane into another mixer and mixing them evenly to obtain a second mixture;

[0110] The first mixed material is added into the main feeding port of the parallel twin-screw extruder through a feeder, and the second mixed material is added into the side of the extruder, and the special glass fiber is added into the other side for melt extrusion and granulation to obtain the PPS / LCP composition.

[0111] The process parameters of the parallel twin-screw extruder are: the temperature of zone 1 is 305℃, the temperature of zone 2 is 305℃, the temperature of zone 3 is 310℃, the temperature of zone 4 is 310℃, the temperature of zone 5 is 315℃, the temperature of zone 6 is 315℃, the temperature of zone 7 is 320℃, the temperature of zone 8 is 320℃, the die head temperature is 315℃, and the screw speed is 500rpm.

[0112] Comparative Example 6

[0113] The following components were weighed and set aside: 54 parts of PPS resin, 10 parts of LCP resin, 20 parts of special glass fiber, 3 parts of double-grafted SEBS, 11 parts of basic copper phosphate, 2 parts of γ-aminopropyltriethoxysilane, and 0.6 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite;

[0114] PPS resin, LCP resin, double-grafted SEBS and bis(2,4-dicumylphenyl)pentaerythritol diphosphite are added into a mixer and mixed to obtain a first mixture;

[0115] Basic copper phosphate and γ-aminopropyltriethoxysilane are added into another mixer and mixed evenly to obtain a second mixture;

[0116] The first mixed material is added into the main feeding port of the parallel twin-screw extruder through a feeder, and the second mixed material is added into the side of the extruder, and the special glass fiber is added into the other side for melt extrusion and granulation to obtain the PPS / LCP composition.

[0117] The process parameters of the parallel twin-screw extruder are: the temperature of zone 1 is 305℃, the temperature of zone 2 is 305℃, the temperature of zone 3 is 310℃, the temperature of zone 4 is 310℃, the temperature of zone 5 is 315℃, the temperature of zone 6 is 315℃, the temperature of zone 7 is 320℃, the temperature of zone 8 is 320℃, the die head temperature is 315℃, and the screw speed is 500rpm.

[0118] The laser direct structuring PPS compositions prepared in the above examples and comparative examples were subjected to the following performance tests:

[0119] Tensile strength: tested according to GB / T 1040-2006 standard, the tensile rate is 50mm / min.

[0120] Notched impact strength: tested in accordance with GB / T 1843-2008 standard.

[0121] Dielectric constant: Tested according to GB / T 5597-1999 standard, test frequency 5GHz.

[0122] Laser direct formability: Adopt the adhesion test of metal coating on the surface of plastic parts (or called hundred-grid test) according to ASTM D3359 standard test, as follows: at room temperature of 23±2℃ and relative humidity of 50±5%, use a sharp blade (blade angle of 15°~30°) to draw 10×10 1mm×1mm small grids on the surface of the test sample, and each line is deep enough to reach the bottom layer of the coating; brush the test area clean; use 3M No. 600 tape to firmly stick to the small grid to be tested, and use an eraser to wipe the tape vigorously to increase the contact area and strength between the tape and the tested area; grab one end of the tape with your hand, and quickly tear off the transparent tape at a 60° angle in the vertical direction, and perform the same test twice at the same position. Result determination: Adhesion is qualified when it is ≥4B; 5B-the edge of the line is smooth, and there is no paint falling off at the edge and intersection of the line; 4B-small pieces of paint fall off at the intersection of the line, and the total falling area is less than 5%; 3B-small pieces of paint fall off at the edge and intersection of the line, and the total falling area is between 5% and 15%; 2B-large pieces of paint fall off at the edge and intersection of the line, and the total falling area is between 15% and 35%; 1B-large pieces of paint fall off at the edge and intersection of the line, and the total falling area is between 35% and 65%; 0B-large pieces of paint fall off at the edge and intersection of the line, and the total falling area is greater than 65%.

[0123] The performance test results are shown in Table 1.

[0124] Table 1

[0125]

[0126] It can be seen from Table 1 that as the amount of special glass fiber added decreases, the tensile strength and notched impact strength of the PPS-based LDS composition decrease. This is mainly because the connection on the interface between glass fiber and resin must transmit the force acting on the molded part to the glass fiber, and the glass fiber bears most of the force, thereby strengthening the resin. At the same time, when impacted by external force, the glass fiber can not only absorb the impact energy, but also induce the generation of silver streaks-shear bands, thereby absorbing a large amount of impact energy.

[0127] In addition, it can be seen from Examples 1 to 5 that the use of any one of basic copper phosphate, copper chrome black, zinc hydroxystannate, and tin oxide in combination with functionalized multi-walled carbon nanotubes can synergistically improve the laser direct formability of the PPS / LCP composition. The key to achieving laser direct forming technology is to add one or more laser-sensitive substances to the resin matrix. This laser direct formability functional additive is generally a metal compound, which can be decomposed into metal particles and other ligands after high-energy laser irradiation. On the one hand, the metal particles exposed on the surface of the material provide catalytic activation centers for subsequent chemical plating to promote the metal in the chemical plating solution to form a new type of structure. Ions are deposited in the laser-irradiated area to form a conductive pattern. On the other hand, the metal particles also have the effect of increasing the bonding strength between the coating and the resin matrix; Cu / Zn / Sn formed after the basic copper phosphate, copper chrome black, zinc hydroxystannate, tin oxide, etc. are excited has good absorption performance for lasers of different wavelengths, which is conducive to LDS molding. After compounding with functionalized multi-walled carbon nanotubes, on the one hand, Zn formed by laser irradiation on the surface of functionalized multi-walled carbon nanotubes also has good absorption performance for lasers. In addition, multi-walled carbon nanotubes themselves have a certain conductivity, which can promote the formation of a conductive network and further promote the formation of a conductive pattern. The adhesion test of the metal coating on the surface of the plastic parts of Examples 1 to 5 reached 5B. It can be seen from Example 1 and Comparative Example 1 that when the special glass fiber is replaced by ordinary glass fiber, its dielectric constant increases significantly; it can be seen from Example 1 and Comparative Example 2 that when the LCP resin is removed from the system, the mechanical properties of the material are reduced, the dielectric constant is also increased, and the laser direct formability is slightly reduced. This is because in the composite material, polyphenylene sulfide and liquid crystal polymer complement each other, which not only improves the toughness and crystallization rate of PPS, but also improves the strength and rigidity of LCP, so it has excellent comprehensive performance; it can be seen from Example 1 and Comparative Example 3 that since the grafting rate of glycidyl methacrylate of the double-grafted SEBS is 1-1.4wt%, and the grafting rate of maleic anhydride is 1-1.4wt%, wherein, The hydrogenated styrene-butadiene-styrene structural unit has very good compatibility with polyphenylene sulfide resin, and the epoxy group of the grafted glycidyl methacrylate and the maleic anhydride group of the grafted maleic anhydride can provide good interface compatibility for PPS resin and LCP resin, as well as compatibility and dispersibility with γ-aminopropyltriethoxysilane, functionalized multi-walled carbon nanotubes, and basic copper phosphate, thereby improving the comprehensive performance of the composite material; It can be seen from Example 1 and Comparative Example 4 that when the surface of the multi-walled carbon nanotubes is not functionalized, on the one hand, it lacks good compatibility with the resin, and on the other hand, the surface of the conductive path of the multi-walled carbon nanotube lacks Zn, an element with a high absorption rate for near-infrared laser, thereby affecting the laser formability of the composite material.

[0128] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0129] Therefore, the above description is only a preferred embodiment of the present application and is not intended to limit the scope of implementation of the present application; that is, all equivalent changes made according to the scope of the claims of the present application are within the protection scope of the claims of the present application.

Claims

1. A PPS / LCP composition, characterized in that: It is prepared from the following components in parts by weight: The laser sensitizer A is a functionalized multi-walled carbon nanotube, and the laser sensitizer B is any one of basic copper phosphate, copper chromium black, zinc hydroxystannate, and tin oxide.

2. The PPS / LCP composition according to claim 1, characterized in that The number average relative molecular mass of the PPS resin is 15000-25000.

3. The PPS / LCP composition according to claim 1, characterized in that The LCP resin is a thermotropic liquid crystal polymer.

4. The PPS / LCP composition according to claim 1, characterized in that The dielectric constant of the special glass fiber is 3.5-4.0, the cross-section length is 26-30 μm, the width is 6.5-7.5 μm, and the flatness ratio is 4:

1.

5. The PPS / LCP composition according to claim 1, characterized in that The compatibilizer is double-grafted SEBS; the double-grafted SEBS is hydrogenated styrene-butadiene-styrene copolymer double-grafted with glycidyl methacrylate and maleic anhydride.

6. The PPS / LCP composition according to claim 1, characterized in that The coupling agent is gamma-aminopropyltriethoxysilane; and the antioxidant is bis(2,4-dicumylphenyl)pentaerythritol diphosphite.

7. The PPS / LCP composition according to claim 1, characterized in that The preparation method of the functionalized multi-walled carbon nanotubes is as follows: (1) uniformly dispersing multi-walled carbon nanotubes and nano zinc oxide in anhydrous ethanol at a mass ratio of 100:10-20, and filtering to obtain an intermediate product; (2) The intermediate product is mixed with an acrylic acid solution, butyl titanate, and an aqueous ammonium persulfate solution, and the mixture is vacuumed and reacted at 90-100° C. in a nitrogen atmosphere for 2-4 hours. After cooling to room temperature, the reaction product is washed, filtered, and dried to obtain functionalized multi-walled carbon nanotubes.

8. The PPS / LCP composition according to claim 7, characterized in that In the acrylic acid solution, the volume ratio of acrylic acid, deionized water and anhydrous ethanol is 1:(0.3-0.5):(0.2-0.4); and the mass concentration of the ammonium persulfate aqueous solution is 4-6wt%.

9. The PPS / LCP composition according to claim 7, characterized in that: In step (2), the mass ratio of the intermediate product, acrylic acid solution, butyl titanate, and ammonium persulfate aqueous solution is 100:(450-500):(1-3):(2-5).

10. The method for preparing the PPS / LCP composition according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) PPS resin, LCP resin, double-grafted SEBS and bis(2,4-dicumylphenyl)pentaerythritol diphosphite are uniformly mixed to obtain a first mixed material; (2) mixing the functionalized multi-walled carbon nanotubes, basic copper phosphate, and γ-aminopropyltriethoxysilane to obtain a second mixture; (3) adding the first mixed material into the main feed port of a parallel twin-screw extruder, adding the second mixed material into the side of the extruder, and adding special glass fiber into the other side, performing melt extrusion, and granulation to obtain a PPS / LCP composition; Among them: the temperature of zone 1 is 300-310°C, the temperature of zone 2 is 300-310°C, the temperature of zone 3 is 305-315°C, the temperature of zone 4 is 305-315°C, the temperature of zone 5 is 310-320°C, the temperature of zone 6 is 310-320°C, the temperature of zone 7 is 315-325°C, the temperature of zone 8 is 315-325°C, the temperature of die head is 310-320°C, and the screw speed is 400-600rpm.

Citation Information

Patent Citations

  • Nylon / polyphenylene sulfide alloy material and preparation method thereof

    CN109852051A

  • Modified resin composition for depositing metal film as well as preparation method and application of modified resin composition

    CN103540151A

  • Thermal conducting material capable of selectively depositing metal, preparation method of the material and applications of the material

    CN103694697A

  • LCP / PPS composite material and preparation method therefor

    CN107400361A

  • Flame-retardant PC composition with a heat conduction function based on an LDS technology and application of flame-retardant PC composition

    CN112920589A

Cited By

  • Flame-retardant and low dielectric loss pps composite, preparation process

    CN122878752A